Moraxella catarrhalis Might Be More Common than Expected in Acute Otitis Media in Young Finnish Children - Sillanpää, Saara; Oikarinen, Sami; Sipilä, Markku; Kramna, Lenka; Rautiainen, Markus; Huhtala, Heini; Aittoniemi, Janne; Laranne, Jussi; Hyöty, Heikki; Cinek, Ondrej (Journal of clinical microbiology, 2016)
According to studies based on bacterial cultures of middle ear fluids, Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis have been the most common pathogens in acute otitis media. However, bacterial culture can be affected by reduced viability or suboptimal growth of bacteria. PCR detects bacterial DNA from samples with greater sensitivity than culture. In the present study, we analyzed the middle ear pathogens with both conventional culture and semiquantitative real-time PCR in 90 middle ear fluid samples obtained from children aged 5 to 42 months during acute otitis media episodes. Samples were tested for the presence of S. pneumoniae, H. influenzae, M. catarrhalis, Alloiococcus otitidis, Staphylococcus aureus, and Pseudomonas aeruginosa One or more bacterial pathogens were detected in 42 (47%) samples with culture and in 69 (77%) samples with PCR. According to PCR analysis, M. catarrhalis results were positive in 42 (47%) samples, H. influenzae in 30 (33%), S. pneumoniae in 27 (30%), A. otitidis in 6 (6.7%), S. aureus in 5 (5.6%), and P. aeruginosa in 1 (1.1%). Multibacterial etiology was seen in 34 (38%) samples, and M. catarrhalis was detected in most (85%) of those cases. Fifteen signals for M. catarrhalis were strong, suggesting a highly probable etiological role of the pathogen. In conclusion, even though M. catarrhalis is often a part of mixed flora in acute otitis media, a considerable proportion of cases may be primarily attributable to this pathogen.
Keywords: bakteriologické techniky; Male; Child, Preschool; kvantitativní polymerázová řetězová reakce; Gram-Negative Bacterial Infections; otitis media; Otitis Media; Infant; Moraxella catarrhalis; prevalence; mužské pohlaví; Coinfection; Real-Time Polymerase Chain Reaction; předškolní dítě; lidé; grampozitivní bakteriální infekce; ženské pohlaví; Gram-Positive Bacterial Infections; Humans; gramnegativní bakteriální infekce; kojenec; Prevalence; koinfekce; Finsko; Female; Finland; Bacteriological Techniques